An oncolytic adenovirus regulated by a radiation‐inducible promoter selectively mediates hSulf‐1 gene expression and mutually reinforces antitumor activity of I131‐metuximab in hepatocellular carcinoma. Issue 3 (7th November 2012) - Zhang, Yan; Fang, Lin; Zhang, Quan'an; Zheng, Qin; Tong, Jinlong; Fu, Xiaohui; Jiang, Xiaoqing; Su, Changqing; Zheng, Junnian
Abstract : Gene therapy and antibody approaches are crucial auxiliary strategies for hepatocellular carcinoma (HCC) treatment. Previously, we established a survivin promoter‐regulated oncolytic adenovirus that has inhibitory effect on HCC growth. The human sulfatase‐1 (hSulf‐1) gene can suppress the growth factor signaling pathways, then inhibit the proliferation of cancer cells and enhance cellular sensitivity to radiotherapy and chemotherapy. I131‐metuximab (I131‐mab) is a monoclonal anti‐HCC antibody that conjugated to I131 and specifically recognizes the HAb18G/CD147 antigen on HCC cells. To integrate the oncolytic adenovirus‐based gene therapy and the I131‐mab‐based radioimmunotherapy, this study combined the CArG element of early growth response‐l (Egr‐l) gene with the survivin promoter to construct a radiation‐inducible enhanced promoter, which was used to recombine a radiation‐inducible oncolytic adenovirus as hSulf‐1 gene vector. When I131‐mab was incorporated into the treatment regimen, not only could the antibody produce radioimmunotherapeutic effect, but the I131 radiation was able to further boost adenoviral proliferation. We demonstrated that the CArG‐enhanced survivin promoter markedly improved the proliferative activity of the oncolytic adenovirus in HCC cells, thereby augmenting hSulf‐1 expression and inducing cancer cell apoptosis. This novel strategy that involved multiple, synergistic mechanisms, including oncolytic therapy, gene therapy and radioimmunotherapy, was demonstrated to exert an excellent anti‐cancer outcome, which will be a promising approach in HCC treatment. Highlights: ► A radiation‐induced oncolytic adenovirus is constructed as hSulf‐1 gene vector. ► I 131 ‐metuximab boosts oncolytic adenoviral proliferation in hepatocellular carcinoma. ► I 131 ‐metuximab increases adenovirus‐mediated hSulf‐1 expression in cancer cells. ► Oncolytic adenovirus and I 131 ‐metuximab synergistically increase antitumor effect.